Pengembangan Aplikasi Pengelola Referensi Skripsi Mahasiswa Universitas Negeri Malang berbasis Personal Information Management - Hisyam Manusakerti; Moh. Safii; Didin Widyartono (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The compilation of reference documents for the thesis can be collected in large numbers. Documents collected in large numbers that not accompanied by good document management can cause "Messy Work Environment". PIM (Personal Information Management) can be used in the management of thesis reference documents. This study used a R&D method. The research data collection technique used semi-structured interviews. Information selected using purposive sampling technique, based on this technique obtained ten information status as students of the State University of Malang who are currently working on their thesis. Data analysis techniques using qualitative data analysis techniques from Miles and Huberman. From the research conducted, it can be seen that some of the main points in each PIM process belong to information such as brief considerations in selecting documents to be stored, using storage methods, and using search and search through search engines as strategies to return to documents.